Technology-enhanced maintenance of treatment gains in eating disorders: efficacy of an intervention delivered via text messaging - Bauer, Stephanie; Kordy, Hans (Journal of consulting and clinical psychology, 2012)
Advances in technology increasingly facilitate data collection in the context of psychosocial and psychotherapeutic care. Such technology-enhanced assessments (e.g. via Internet-based systems and mobile devices) open new perspectives for research into processes related to mental health and well-being. The use of this knowledge for the development and refinement of (online and face-to-face) therapeutic interventions promises to contribute to an optimization of care. The aim of this paper is to provide an overview on how information and communication technologies may be used (a) to improve our understanding of illness development and recovery through longitudinal technology-enhanced assessment of symptoms and behaviors (e.g. outcome monitoring and ecological momentary assessment) and (b) to optimize care for mental disorders by integrating such monitoring assessments in specific interventions (e.g. ecological momentary interventions and supportive monitoring) in face-to-face or e-mental health settings.
Gesehen am 08.11.2018